2019
DOI: 10.1007/s11242-019-01323-w
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Solvers for Large-Scale Coupled Problems in Porous Media

Abstract: This work summarizes solution strategies for discrete systems occurring in the simulation of processes in the subsurface. The focus is on scalable solvers for large and coupled systems. The goal of this work is to enable researchers to select suitable algorithms and parameter settings to efficiently solve their problems. The work provides an overview of existing methods, highlighting their features, potential, and also frequent pitfalls. Numerical examples are provided for single phase flow, density driven flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…For a glossary of common terms and information on multiphysics simulations in general, the reader is referred to a respective review [32]. Moreover, a recent review on conjugate heat transfer simulations can be found in [33], and solvers for coupled porous media flow have recently been reviewed in [34].…”
Section: Introductionmentioning
confidence: 99%
“…For a glossary of common terms and information on multiphysics simulations in general, the reader is referred to a respective review [32]. Moreover, a recent review on conjugate heat transfer simulations can be found in [33], and solvers for coupled porous media flow have recently been reviewed in [34].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the more conventional time-stepping methods or tensorstructured space-time methods [18,19,28], this unstructured space-time approach provides us with more flexibility in constructing parallel space-time solvers such as parallel space-time algebraic multigrid preconditioners [24] or space-time balancing domain decomposition by constraints (BDDC) preconditioners [26]. Moreover, it becomes more convenient to realize simultaneous space-time adaptivity on unstructured space-time meshes [24,25,33] than the other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Other articles address experimental issues-at the macroscale (Falzone et al 2018) and fluid displacement at the pore scale (Gerami et al 2018), while Armstrong et al (2018) demonstrates how one can go from X-ray microcomputed tomography to characterizing porous media for modeling. And two articles address computational issues: one about open-source software (Bilke et al 2019) and one about numerical algorithms for large-scale porous media problems (Nägel et al 2019). Unfortunately, there are some topics that are not addressed in this issue.…”
mentioning
confidence: 99%